Pertimbangan Hakim dalam Menjatuhkan Hukuman Ringan pada Kasus Perjudian (Studi Putusan Nomor 65 /PID.B/2013 /PN.LBJ) - Samara, Finsensius; Rabawati, Dwityas Witarti; Kelen, Rosalia Martha Jawa; Umar, Sonya Prisilia; Bukifan, Francisco Tolentino Bukifan; Oelue, Jeremias (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: In 2024, Indonesia remains among the ten Asian countries with the lowest income. PPATK data reveals that 2.2 million low-income Indonesians are gamblers, threatening the vision of Indonesia Emas 2045. Gambling, categorized as a crime under Articles 303 of the Indonesian Criminal Code (KUHP), causes significant losses.Purposes of the Research: The objective of this research is to analyze the judge's considerations in giving light sentences in gambling cases, specifically those involving the offering of gambling games, using Decision Number 65/PID.B/2013/PN.LBJ as a case study.Methods of the Research: This research employs a normative legal research method with an analytical approach. The analysis is conducted on legal norms, court decisions, and related literature to understand the judge's considerations in the case.Results of the Research: The findings show that although the defendant fulfilled the elements of Article 303 of the KUHP, the judge considered mitigating circumstances, such as the defendant's age, pregnancy, respectful demeanor in court, admission of guilt, and remorse. The judge balanced legal certainty with justice and utility, demonstrating an educative and preventive approach in sentencing